Concurrent assessment of time-to-isolation and temperature at 30 s as an innovative metric for predicting the persistence of pulmonary vein isolation using second-generation cryoballoons - Mei-Qiong Wu; Lin Chen; Liang-Hua Lian; Jian-Quan Chen; Yi-Ming Peng; Xue-Wen Liao; Ya-Zhou Lin; Jian-Cheng Zhang (Journal of Cardiothoracic Surgery)
Abstract Background We attempted to establish correlations between intraoperative variables such as time-to-isolation (TTI) and temperature (T) at the 30-second mark, and the sustained efficacy of pulmonary vein isolation. Methods One hundred patients underwent repeat procedures subsequent to their index ablation. Five time intervals were delineated based on TTI metrics of 30, 35, 40, 45, and 60 s during the initial procedure. Subsequently, temperatures of -25 °C, -29 °C, -30 °C, and − 31 °C were determined at 30 nodes during repeat procedures, guided by the findings from the initial intervention. The prevalence of re-established pulmonary vein (PV) potentials was assessed both prior to and post each TTI and temperature assessment at the 30-second node. Results The incidence of reconnected PV potentials demonstrated a noteworthy reduction in the group with TTI < 30 s group than in the TTI ≥ 30. Similarly, there was a notable decrease in the incidence of reconnected PV potentials in the group with T at 30 s of < -31 ℃ than ≥ -31 ℃. The sensitivity, specificity, and positive predictive values (PPVs) for predicting durable pulmonary vein isolation were 13.19%, 94.44%, and 83.72%, respectively, in cases where the TTI was < 30 s and T at 30 s was < -31 ℃. Conclusion Integrating both TTI30s and T30s could potentially serve as an effective method for predicting the persistence of pulmonary vein isolation using second-generation cryoballoons.